1971
DOI: 10.3109/00207457109146980
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gaba and Other Amino Acids In Different Tissues of The Gastropod Mollusc Helix Pomatia, Including In Vitro Experiments With,4c Glucose andI4c Glutamic Acid

Abstract: Microchromatography on 3 x 3 cm polyamide layers of dansyl-compounds was used to study the distribution of free amino acids, GABA, serotonin, 5-hydroxyindole and 5-hydroxytryptophan in the brain, optic tentacle, pharyngeal retractor muscle and heart of Helix pomuriu. In addition the formation of GABA after incubation in U-I r C glucose or U-*rC glutamic acid was studied.Low amounts of GABA were for the first time shown to occur in all four tissues studied. In addition taurine, thought to be absent from terrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The presence of GABA in the molluscan central nervous system was first shown in the cephalopod, Eledone cirrhosa (Bradford et al, 1969;Cory and Rose, 1969), and subsequently demonstrated in the pulmonates Helix pomatia (Osborne et al, 1971;Dolezalova et al, 1973), Helix aspersa (Osborne, 1971), Achatina fulica (Takeuchi et al, 1977), and Helisoma trivolvis (Richmond et al, 1991). Of particular relevance to the present study are the findings of Cottrell (1974) who measured GABA levels in the various ganglia of Aplysia dactylomela.…”
Section: Gabaergic Systems In Molluscsmentioning
confidence: 62%
See 1 more Smart Citation
“…The presence of GABA in the molluscan central nervous system was first shown in the cephalopod, Eledone cirrhosa (Bradford et al, 1969;Cory and Rose, 1969), and subsequently demonstrated in the pulmonates Helix pomatia (Osborne et al, 1971;Dolezalova et al, 1973), Helix aspersa (Osborne, 1971), Achatina fulica (Takeuchi et al, 1977), and Helisoma trivolvis (Richmond et al, 1991). Of particular relevance to the present study are the findings of Cottrell (1974) who measured GABA levels in the various ganglia of Aplysia dactylomela.…”
Section: Gabaergic Systems In Molluscsmentioning
confidence: 62%
“…Biochemical approaches demonstrated the presence of GABA, its synthesis, and its uptake in the central nervous systems of several molluscan species (Osborne et al, 1971;Dolezalova et al, 1973;Cottrell, 1974). The localization of GABA to specific neurons within molluscan nervous systems was shown by using autoradiographic and immunohistological techniques (Turner and Cottrell, 1978;Cooke and Gelperin, 1988;Richmond et al, 1991;Arshavsky et al, 1993;Hernadi, 1994;Norekian, 1999).…”
mentioning
confidence: 99%
“…While we likely uncovered a great proportion of the larval nervous system in I. obsoleta, still other neurons may exist. This seems especially likely since additional classical transmitters, such as acetylcholine (Twarog, 1954;Hanley and Cottrell, 1974;Chrachri and Williamson, 1998), GABA (Osborne et al, 1972;Walker et al, 1975;Morse et al, 1980;Cooke and Gelperin, 1988;Vitellaro-Zuccarello and De Biasi, 1988), and glutamate (Bolshakov et al, 1991;Dale and Kandel, 1993;Nesic et al, 1996;Michel et al, 2000) as well as various peptides (Croll and Van Minnen, 1992;Santama et al, 1994;Willows et al, 1997) are utilized in adult molluscan neurons. Furthermore, we have recently localized histamine in larval stages of I. obsoleta (unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…A microbiochemical method (Neuhoff, 1971;Osborne, Briel & Neuhoff, 1971) was used in this study to observe the metabolism of [14C]-tryptophan in two specific types of giant cells in the snail Helix pomatia. One type of cell (GSC) situated in each cerebral ganglion is known to contain 5-hydroxytryptamine (Cottrell & Osborne, 1970), while the other, situated in each buccal ganglion, lacks this amine (Osborne & Cottrell, 1972a (Osborne, 1972a) and that both cell types contain tryptophan (Briel, Neuhoff & Osborne, 1972;Osborne & Cottrell, 1972a).…”
mentioning
confidence: 99%